2011
DOI: 10.1080/00028487.2011.607036
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Development and Related Observations during the Spawning Migration of Hickory Shad

Abstract: Hickory shad Alosa mediocris were sampled for two consecutive years in coastal North Carolina at various points of their ascent in salt water, brackish water, and freshwater to examine reproductive development and related variables during the spawning migration. Fish averaged 3 years of age; however, the proportion of repeat spawners and the proportion of individuals in older age‐classes were greater for females than for males, and females were larger than males of the same age. Nearly all fish had identifiabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 14 publications
3
31
1
Order By: Relevance
“…Seasonal timing of spawning was similar to that expected from spawning elsewhere along the U.S. East Coast, give or take a month. For instance, results from this study observed Hickory Shad spawning through late May, which is little over a month later than reported by Marshall (1976) and Murauskas and Rulifson (2011). Spawning of American Shad was similar to that reported by Harris and Hightower (2011b).…”
Section: Spawning Rangessupporting
confidence: 82%
“…Seasonal timing of spawning was similar to that expected from spawning elsewhere along the U.S. East Coast, give or take a month. For instance, results from this study observed Hickory Shad spawning through late May, which is little over a month later than reported by Marshall (1976) and Murauskas and Rulifson (2011). Spawning of American Shad was similar to that reported by Harris and Hightower (2011b).…”
Section: Spawning Rangessupporting
confidence: 82%
“…the reproductive success of other imperiled anadromous fishes, such as alosines (e.g., Murauskas and Rulifson 2011) and Striped Bass (Rulifson and Dadswell 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reproductive investment is complete prior to migration in a population of American Shad found at a higher latitude (Glebe and Leggett 1981). Murauskas and Rulifson (2011) suggested that Hickory Shad in North Carolina, spawning every 3 d over a 2-to 4-week season, must be spawning batches of oocytes that recruited after the spawning season commenced.…”
Section: Indeterminate Fecundity In Alewivesmentioning
confidence: 99%